Structure-based design of novel heterocycle-substituted ATDP analogs as non-nucleoside reverse transcriptase inhibitors with improved selectivity and solubility - Li-Min Zhao; Christophe Pannecouque; Erik De Clercq; Shuai Wang; Fen-Er Chen (Elsevier, 2023)
Following on our recently developed biphenyl-ATDP non-nucleoside reverse transcriptase inhibitor ZLM-66 (SI = 2019.80, S = 1.9 μg/mL), a series of novel heterocycle-substituted ATDP derivatives with significantly improved selectivity and solubility were identified by replacement of the biphenyl moiety of ZLM-66 with heterocyclic group with lower lipophilicity. Evidently, the representative analog 7w in this series exhibited dramatically enhanced selectivity and solubility (SI = 12,497.73, S = 4472 μg/mL) in comparison with ZLM-66 (SI = 2019.80, S = 1.9 μg/mL). This new NNRTI conferred low nanomolar inhibition of wild-type HIV-1 strain and tested mutant strains (K103N, L100I, Y181C, E138K, and K103N + Y181C). The analog also demonstrated favorable safety and pharmacokinetic profiles, as evidenced by its insensitivity to CYP and hERG, lack of mortality and pathological damage, and good oral bioavailability in rats (F = 27.1%). Further development of 7w for HIV therapy will be facilitated by this valuable information.